2013
DOI: 10.1158/1535-7163.mct-12-0529
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CXCR2 Enhances Chemotherapeutic Response, Inhibits Mammary Tumor Growth, Angiogenesis, and Lung Metastasis

Abstract: Breast cancer is one of the leading causes of cancer deaths among females. Many challenges exist in the current management of advanced stage breast cancer as there are fewer recognized therapeutic strategies, often due to therapy resistance. How breast cancer cells evade chemotherapy and the underlying mechanism remains unclear. We and others have observed that malignant cells that survive initial chemo-and radiation therapy express higher levels of CXCR2 ligands which might provide a survival benefit leading … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
91
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 42 publications
8
91
0
Order By: Relevance
“…The IL8-CXCR2 pathway has been shown to be important in the pathogenesis of solid tumors, and preclinical studies have demonstrated a role for this pathway in the breast cancer microenvironment. 22,27,28,30,45 Various small molecule CXCR2 inhibitors are being developed clinically, and one is being tested in a clinical trial in breast cancer. Our results demonstrate that this pathway is also functionally important for the viability of leukemic stem cell compartments in AML and MDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IL8-CXCR2 pathway has been shown to be important in the pathogenesis of solid tumors, and preclinical studies have demonstrated a role for this pathway in the breast cancer microenvironment. 22,27,28,30,45 Various small molecule CXCR2 inhibitors are being developed clinically, and one is being tested in a clinical trial in breast cancer. Our results demonstrate that this pathway is also functionally important for the viability of leukemic stem cell compartments in AML and MDS.…”
Section: Discussionmentioning
confidence: 99%
“…IL8 is a known potent proinflammatory cytokine that exerts its effects through binding to its G protein-coupled receptors CXCR1 and CXCR2. Extensive work in solid tumors has shown that IL8 is critical in survival, invasion, and proliferation of cancer cells [21][22][23][24] and might be an important regulator of cancer stem cell activity. [25][26][27] Activation of multiple pathways by IL8, including phosphatidylinositol 3-kinase/protein kinase B (AKT), phospholipase C/protein kinase C, and mitogen-activated protein kinase (MAPK) signaling, leads to increased expression of various The online version of this article contains a data supplement.…”
Section: Introductionmentioning
confidence: 99%
“…chemotherapy against breast tumors and particularly against metastatic activity [40]. Knockdown of CXCR2 was also found to enhance the antitumor activity of paclitaxel in an in vivo mammary tumor model [41]. Anti-VEGF therapy is in clinical use for the treatment of GC [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The chemokine receptor CXCR2 is considered a key molecular target for the diagnosis and treatment of a variety of acute and chronic inflammatory diseases such as chronic obstructive pulmonary disease, asthma, fibrosis, psoriasis, multiple sclerosis, cystic fibrosis, rheumatoid arthritis, inflammatory bowel disease, allograft rejection, and angiogenesis and also in cancer metastasis (Stadtmann and Zarbock, 2012;Hertzer et al, 2013;Sharma et al, 2013). CXCR2 is a G proteincoupled receptor (GPCR) that is expressed on many different cells and tissues, including neutrophils, mast cells, CD8…”
Section: Introductionmentioning
confidence: 99%